Evaluasi Analisis Capaian Pembelajaran Lulusan melalui Sistem Informasi CPL Berbasis OBE - Bintoro, Henry Suryo; Gudnanto, Gudnanto; Ruby, Arcivid Chorynia; Ratri, Prapti Madyo; Romadhon, Zainur (Universitas Muhammadiyah Magelang, 2026)
This study aims to evaluate and analyze Graduate Learning Outcomes (CPL) through the development and implementation of an information system for CPL measurement based on the Outcome-Based Education (OBE) curriculum. The research employed a development research approach using the prototype model, combined with rubric-based evaluation and academic data analysis. Data were collected through observation, interviews, documentation review, literature study, and the utilization of academic records and graduate tracer studies. Data analysis was conducted using descriptive quantitative and qualitative techniques to examine the achievement of CPL in the aspects of knowledge, skills, and attitudes. The results indicate that the majority of graduates have achieved the expected learning outcomes, with an average Grade Point Average (GPA) of 3.5, knowledge achievement of 87%, skills achievement of 82%, and professional attitude achievement of 93%. The developed information system is able to present CPL achievement data in an integrated and real-time manner, supporting quality evaluation and accreditation requirements. This study concludes that the OBE-based CPL measurement information system is effective as an internal quality assurance and evaluation tool and serves as a foundation for continuous improvement of curriculum and learning strategies in higher education institutions.